Bonifacio de' Pitati - Cottrell, Philip; Humfrey, Peter 1947- (ZeL Edizioni, 2021)
This is the first major study of the prolific Venetian Renaissance painter Bonifacio de’ Pitati (aka Bonifacio Veronese) (1487-1553) for almost a century. A contemporary and rival of Titian, Bonifacio represented a progressive and influential force in the painting of the lagoon in the middle decades of the sixteenth century. Constantly in demand as a decorator of state offices and churches, Bonifacio was also a specialist in scenes of holy gatherings set in idyllic countryside settings for domestic interiors. These complement his pioneering development of large panoramic narratives for Venetian palaces which reflect the glamorous gentrification of Venetian society and the development of its mainland villa culture. In terms of their approach to colour, landscape and descriptive detail, these are among the most beautiful of their era. The first half of the book comprises a series of essays covering the chronological development of Bonifacio’s career within the wider context of Venetian Renaissance painting by Philip Cottrell. This prefaces a detailed catalogue raisonné of over two-hundred of Bonifacio’s paintings by Peter Humfrey, including recent discoveries, discussed and illustrated for the first time. In acknowledgement of Bonifacio’s reputation as one of the great colourists of the Venetian school, the book is richly illustrated with nearly three-hundred colour illustrations of works of art by Bonifacio and his contemporaries. Cottrell and Humfrey also supply appendices of documents associated with Bonifacio’s life and work, a register of pictures connected to artists of his workshop and numerous original reconstructive diagrams of Bonifacio’s extensive painted decoration of Venice’s state offices
© 2021 ZeL Edizioni. Printed by ZeL Edizioni Europrint, Quinto di Treviso (TV) September 2023
Keywords: Bonifazio -- Veronese -- 1487-1553; Malerei; Katalog